S.M.A.C. (copy of statement)
C02-0012-001 S.M.A.C'tee COPY. The Trustees of the Spanish Medical Aid Committee, having consulted together on an application from the Secretary of the National Trade Union Club, London, to stand guarantee to its Bank jointly with other persons, but the Committee's liability only to amount to £35 (Thirty-five pounds), agrees unanimously, in view of this Club's services to the Committee at its inception, to cover its Chairman ( Dr. H. B. Morgan ) to this amount in his personal guarantee on behalf of the Committee in accordance with the wishes of the Bank ( Co-operative Wholesale Society Bank ). Posted with letter to Lieut. George Jeger, dated 2.12.40 on 4th December, 1940. - Letter filed in "P." section of File containing Rochdale Constituency letters. Copied EDK. 292C/946/2/12